PENGARUH KUALITAS SISTEM INFORMASI, KUALITAS INFORMASI, PERCEIVED USEFULNESS, TERHADAP KEPUASAN PENGGUNA AKHIR SOFTWARE AKUNTANSI - Kurniawati, Diana; Nurazi, Ridwan; Martiah, Lisa (JURNAL FAIRNESS, 2013)
The objectives of this research was to find the effect of the quality of system information, quality of information and perceived usefulness of accounting software to the satisfaction of the end user. This research was conducted at University of Bengkulu. Data collection with questionnaire that spread out to the respondents by census methodology. Then, the data analyzed using SPSS 16. The analysis that conducted in this research was validity test, reliability, normality, multicoliniearity and heteroscedasticity analysis, to get the data that is valid, reliable, normal,and free from multicolinieraity and heteroscedaticity. The result of analysis showed that for the first hypothetical (H1), the level of significancy the accounting software quality was <0,05 with the standardized beta value 0,370, imply that there is a significant and positive effect of the accounting software quality to the end user. For the second hypothetical (H2), there is total effect value 0,61 with significancy level at <0,05, conclude that there is a significant and positive effect of the accounting software quality to the end user by perceived usefulness. For the third hypothetical (H3), the significancy level of information quality was < 0,05 with the standardized beta value 0,314, imply that there is positive and significant effect of the quality of information to the satisfaction of the end user of accounting software. Finally, for the fourth hypothetical (H4), there is total effect value 0,204 with negative standardized value -0,11 and non significant, conclude that the quality of information have negative effect and not significant at level 0,987 to the satisfaction of the end user of accounting software by perceived usefulness